Adhesive layer, adhesive film for touch panels, optical film with adhesive layer
The adhesive layer, characterized by a specific gel fraction and storage elastic modulus, addresses the challenges of bonding cover glass and sensor glass by providing excellent step-following performance and durability, along with improved optical properties.
Patent Information
- Application Number
- JP2023212298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2035-04-15
AI Technical Summary
Existing adhesive technologies for bonding cover glass and sensor glass in touch panels face challenges such as high costs due to the need for extra adhesive layers, difficulty in ensuring UV curing of the adhesive, and the presence of air bubbles, especially in areas with step formations.
A pressure-sensitive adhesive layer with a gel fraction of 40 to 75% and a storage elastic modulus of 100,000 Pa or less, formed by cross-linking an adhesive composition containing an acrylic polymer and a cross-linking agent, which provides excellent step-following performance and durability.
The adhesive layer achieves excellent step-following performance and durability, ensuring strong bonding between cover glass and sensor glass while minimizing air bubbles and maintaining high optical properties such as light transmittance and low haze.
Smart Images

Figure 0007656685000001 
Figure 0007656685000002 
Figure 0007656685000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive layer and an adhesive film used for bonding a cover glass (or a touch sensor glass) and a sensor glass (or a sensor film) of a touch panel member. More specifically, the present invention relates to an optical adhesive layer that has good step conformability to a frame print arranged on the cover glass and has both excellent step conformability and durability even when the cover glass and the sensor glass are bonded together, and an adhesive film for touch panels and an optical film with an adhesive layer using the same. [Background technology]
[0002] Examples of displays (display devices) to which touch panels are applied include liquid crystal displays (LCDs) and electroluminescence displays (inorganic EL, organic EL), and specific electronic devices in which such touch panels are used include LCD televisions, mobile terminals, mobile phones, electronic paper, e-book terminals, and personal computers.
[0003] For example, Patent Document 1 describes the use of a combination of an impact-resistant and thick pressure-sensitive adhesive layer and an adhesive layer that is less susceptible to air bubbles in order to adhere a light-transmitting member having a step in a light-shielding layer onto a display surface in a liquid crystal device or touch panel. Furthermore, Patent Document 2 describes a method of attaching a transparent adhesive sheet containing a cyclic olefin resin, a saturated polyisobutylene resin, an acrylic resin, a photoinitiator, etc., between a touch panel and a surface protective layer such as a glass plate. Furthermore, Patent Document 3 describes a method for bonding a touch panel and a protective transparent plate using a transparent adhesive sheet containing a polyoxyalkylene polymer having an alkenyl group, a compound having a hydrosilyl group, a hydrosilylation catalyst, etc. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-098324 A [Patent Document 2] JP 2010-072471 A [Patent Document 3] JP 2010-097070 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the display device described in Patent Document 1, bonding a light-transmitting member to the surface of a touch panel via an adhesive layer and a pressure-sensitive adhesive layer requires extra work compared to using only a pressure-sensitive adhesive layer, which increases costs and makes it difficult to adopt for inexpensive display devices. Also, in the display device described in Patent Document 1, a light-shielding layer with a thickness of about 5 to 10 μm is formed so as to surround the outer periphery of the liquid crystal device, but the adhesive layer and pressure-sensitive adhesive layer areas are arranged within the frame of the light-shielding layer so as to avoid the influence of printing steps in the light-shielding layer.
[0006] Patent Document 2 also discloses that a surface protection layer having a light-shielding layer is bonded to the surface of a touch panel via an adhesive layer having a specific storage modulus. It is said that the use of this adhesive layer will not cause air bubbles, but after the surface protection layer is bonded to the touch panel, ultraviolet light is irradiated from the opposite side of the surface protection layer or the touch panel to harden the adhesive, which causes a problem that the back side of the light-shielding layer is not sufficiently irradiated with ultraviolet light.
[0007] Patent Document 3 also discloses that a protective transparent plate having a black printed layer is bonded to the surface of a touch panel via a transparent adhesive sheet having a specific shear storage modulus and gel fraction. It is said that if the transparent adhesive sheet of Patent Document 3 is used, no bubbles will be generated at the adhesive surface between the liquid crystal display panel and the protective transparent plate. However, since the protective transparent plate made of transparent plastic is bonded to the liquid crystal panel via the transparent adhesive sheet, there is a problem that air bubbles cannot be avoided from remaining in the corners where the step of the black printed layer occurs.
[0008] The present invention aims to provide an optical pressure-sensitive adhesive layer that has good step-following ability with respect to a frame print arranged on a cover glass, and that combines excellent step-following ability and durability even when the cover glass and sensor glass are bonded together, and an adhesive film using the same. [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have conducted extensive research and found that when the gel fraction of the adhesive layer and the strain value when a shear force is applied to the adhesive layer are within a predetermined range, both excellent step conformability and durability are achieved. The technical idea of the present invention is to provide an adhesive layer having a gel fraction of 40 to 75%, a storage modulus of 100000 (10 to the power of 5) Pa or less at 1 Hz and 100°C measured by laminating the adhesive layer to a thickness of 1000 μm, a strain of 15% or more when a shear force of 500 Pa is applied continuously for 30 minutes under a load of 1 N, and a strain recovery force of 50% or more thereafter.
[0010] In order to solve the above-mentioned problems, the present invention provides a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, the acrylic polymer being a copolymer obtained by copolymerizing at least one monomer selected from the group of monomers consisting of an alkyl acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, a branched-structure alkyl group-containing monomer, and a nitrogen-containing vinyl monomer, and a hydroxyl group-containing copolymerizable vinyl monomer ... the pressure-sensitive adhesive layer has a gel fraction of 40 to 75%, a storage modulus of 1 Hz and 100°C measured after laminating the pressure-sensitive adhesive layer to a thickness of 1,000 µm is 100,000 Pa or less, and when a shear force of 500 Pa is continuously applied for 30 minutes under a load of 1 N, a strain of 15% or more and a strain recovery force thereafter of 50% or more are provided.
[0011] It is also preferred that the acid value of the acrylic polymer is 1 or less, the pressure-sensitive adhesive composition contains an isocyanate compound as the crosslinking agent in an amount of 0.01 to 3.0 parts by weight per 100 parts by weight of a total of at least one monomer selected from the monomer group, and when the pressure-sensitive adhesive layer after crosslinking the pressure-sensitive adhesive composition is laminated to a thickness of 175 μm on one side of a substrate, the pressure-sensitive adhesive layer has an adhesive strength of 20 N / 25 mm or more, a total light transmittance of 90% or more, and a haze value of 1.0% or less.
[0012] The pressure-sensitive adhesive composition preferably further contains 0.01 to 2.0 parts by weight of a silane coupling agent relative to 100 parts by weight in total of at least one monomer selected from the above monomer group.
[0013] In addition, it is preferable that the hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate.
[0014] It is also preferred that the pressure-sensitive adhesive composition further contains, relative to a total of 100 parts by weight of at least one or more monomers selected from the monomer group, 0.1 to 10 parts by weight of a polyfunctional acrylate monomer having 2 to 3 acryloyl groups in one molecule and 0.01 to 2.0 parts by weight of a photopolymerization initiator, and that the pressure-sensitive adhesive layer after crosslinking the pressure-sensitive adhesive composition is attached to an adherend and then cured by ultraviolet ray irradiation has a gel fraction of 50 to 95%.
[0015] In addition, it is preferable that the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition, and the pressure-sensitive adhesive layer is laminated to an adherend and then cured by ultraviolet irradiation, the pressure-sensitive adhesive composition further contains 0.1 to 10 parts by weight of a polyfunctional acrylate monomer having 2 to 3 acryloyl groups in one molecule and 0.01 to 2.0 parts by weight of a photopolymerization initiator, relative to a total of 100 parts by weight of at least one or more monomers selected from the monomer group, and the gel fraction of the pressure-sensitive adhesive layer after the ultraviolet curing is 50 to 95%.
[0016] The present invention also provides an adhesive film for a touch panel, comprising the above-mentioned adhesive layer laminated on one surface of a substrate.
[0017] The present invention also provides a pressure-sensitive adhesive layer-attached optical film, comprising an optical film and the pressure-sensitive adhesive layer laminated on at least one surface of the optical film. Effect of the Invention
[0018] According to the adhesive layer of the present invention, the gel fraction of the adhesive layer and the strain value when a shear force is applied to the adhesive layer are within a specified range, so that the adhesive layer has good step-following ability to the frame print arranged on the cover glass. Even when the cover glass and the sensor glass are bonded together, an optical adhesive layer and an adhesive film using the same can be provided that combine excellent step-following ability and durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the present invention will be described based on preferred embodiments. The pressure-sensitive adhesive layer of the present invention is a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, the acrylic polymer being a copolymer obtained by copolymerizing at least one monomer selected from a monomer group consisting of an alkyl acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, a branched-structure alkyl group-containing monomer, and a nitrogen-containing vinyl monomer, and a hydroxyl group-containing copolymerizable vinyl monomer, the acrylic polymer containing 0.1 to 10.0 parts by weight of the hydroxyl group-containing copolymerizable vinyl monomer relative to a total of 100 parts by weight of the at least one monomer selected from the monomer group, the pressure-sensitive adhesive layer having a gel fraction of 40 to 75%, a storage modulus of 1 Hz and 100°C measured after laminating the pressure-sensitive adhesive layer to a thickness of 1000 μm is 100,000 Pa or less, a strain of 15% or more when a shear force of 500 Pa is continuously applied for 30 minutes under a load of 1 N, and a strain recovery force of 50% or more thereafter.
[0020] The acrylic polymer of the pressure-sensitive adhesive layer according to the present invention is a copolymer obtained by copolymerizing at least one monomer selected from the group consisting of alkyl acrylate monomers having an alkyl group carbon number of C1 to C14, alicyclic-containing monomers, branched alkyl group-containing monomers, and nitrogen-containing vinyl monomers as the monomers belonging to the first monomer group, and at least one hydroxyl group-containing copolymerizable vinyl monomers as the monomers belonging to the second monomer group, and at least one monomer belonging to the first monomer group and at least one monomer belonging to the second monomer group. In this specification, (meth)acrylate is a general term for acrylate and methacrylate.
[0021] In the adhesive composition of the adhesive layer according to the present invention, the alkyl acrylate monomer having an alkyl group with carbon number of C1 to C14 includes at least one of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, nonyl acrylate, decyl acrylate, undecyl acrylate, dodecyl acrylate, tridecyl acrylate, and tetradecyl acrylate. The alkyl group of the alkyl acrylate monomer may be linear, branched, or cyclic, but the alkyl group here is linear. The acrylate monomer having a branched alkyl group belongs to the branched alkyl group-containing monomer. The acrylate monomer having a cyclic alkyl group belongs to the alicyclic-containing monomer.
[0022] In the pressure-sensitive adhesive composition of the pressure-sensitive adhesive layer according to the present invention, the alicyclic-containing monomer may be at least one of cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicycloheptyl (meth)acrylate, bicyclooctyl (meth)acrylate, dimethylbicycloheptyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc. The alicyclic-containing monomer may be an alicyclic alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C18.
[0023] In the pressure-sensitive adhesive composition of the pressure-sensitive adhesive layer according to the present invention, examples of the branched alkyl group-containing monomer include at least one of isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, isoundecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isotetradecyl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate, isooctadecyl (meth)acrylate, isomyristyl (meth)acrylate, and isostearyl (meth)acrylate. The branched alkyl group-containing monomer may be a branched alkyl (meth)acrylate monomer in which the alkyl group has a carbon number of C1 to C18. The branched alkyl group-containing monomer may have a branched structure in which the alkyl group has two or more branches (for example, two or more side chains to the main chain), such as a t-butyl group.
[0024] In the pressure-sensitive adhesive composition of the pressure-sensitive adhesive layer according to the present invention, examples of the nitrogen-containing vinyl monomer include vinyl monomers containing an amide bond, vinyl monomers containing an amino group, vinyl monomers having a nitrogen-containing heterocyclic structure, etc. More specifically, examples of the nitrogen-containing vinyl monomers include N-vinyl-substituted heterocyclic structures such as N-vinyl-2-pyrrolidone, N-vinylpyrrolidone, methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-vinyllaurylolactam. Cyclic nitrogen-containing vinyl compounds having a heterocyclic structure substituted with N-(meth)acryloyl, such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperazine, N-(meth)acryloylaziridine, N-(meth)acryloylazetidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylpiperidine, N-(meth)acryloylazepane, and N-(meth)acryloylazocane. Cyclic nitrogen-containing vinyl compounds; cyclic nitrogen-containing vinyl compounds having a heterocyclic structure having a nitrogen atom and an ethylenically unsaturated bond in the ring, such as N-cyclohexylmaleimide and N-phenylmaleimide; unsubstituted or monoalkyl-substituted (meth)acrylamides, such as (meth)acrylamide, N-methyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and Nt-butyl(meth)acrylamide; dialkyl-substituted (meth)acrylamides, such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropylacrylamide, N,N-diisopropyl(meth)acrylamide, N,N-dibutyl(meth)acrylamide, N-ethyl-N-methyl(meth)acrylamide, N-methyl-N-propyl(meth)acrylamide, and N-methyl-N-isopropyl(meth)acrylamide;Dialkylamino(meth)acrylates such as N,N-dimethylaminomethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, N,N-dimethylaminoisopropyl(meth)acrylate, N,N-dimethylaminobutyl(meth)acrylate, N,N-diethylaminomethyl(meth)acrylate, N,N-diethylaminoethyl(meth)acrylate, N-ethyl-N-methylaminoethyl(meth)acrylate, N-methyl-N-propylaminoethyl(meth)acrylate, N-methyl-N-isopropylaminoethyl(meth)acrylate, N,N-dibutylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; N,N-dimethylaminopropyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, N N,N-dialkyl-substituted aminopropyl(meth)acrylamide such as N-dipropylaminopropyl(meth)acrylamide, N,N-diisopropylaminopropyl(meth)acrylamide, N-ethyl-N-methylaminopropyl(meth)acrylamide, N-methyl-N-propylaminopropyl(meth)acrylamide, and N-methyl-N-isopropylaminopropyl(meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinylformamide, N-vinylacetamide, and N-vinyl-N-methylacetamide; (meth)acrylamides such as N-methoxymethyl(meth)acrylamide, N-ethoxyethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone acrylamide, and N,N-methylenebis(meth)acrylamide; and unsaturated carboxylic acid nitriles such as (meth)acrylonitrile. Nitrogen-containing vinyl monomer is preferably one that does not contain hydroxyl group, more preferably one that does not contain hydroxyl group and carboxyl group.As such monomer, the above-mentioned monomer is preferable, for example, acrylic monomer containing N,N-dialkyl-substituted amino group or N,N-dialkyl-substituted amide group; N-vinyl-2-pyrrolidone, N-vinylcaprolactam, N-vinyl-2-piperidone and other N-vinyl-substituted lactams; N-(meth)acryloylmorpholine, N-(meth)acryloylpyrrolidine and other N-(meth)acryloyl-substituted cyclic amines.
[0025] In the pressure-sensitive adhesive composition of the pressure-sensitive adhesive layer according to the present invention, examples of the hydroxyl-containing copolymerizable vinyl monomer include at least one of hydroxyl-containing alkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate, and hydroxyl-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. Among these, it is preferable that the hydroxyl-containing copolymerizable vinyl monomer is at least one selected from the group of compounds consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. The acrylic polymer according to the present invention preferably contains 0.1 to 10.0 parts by weight, more preferably 0.2 to 5.0 parts by weight, and particularly preferably 0.2 to 4.0 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer relative to 100 parts by weight of the total of the monomers belonging to the first monomer group.
[0026] In the pressure-sensitive adhesive composition of the pressure-sensitive adhesive layer according to the present invention, the acrylic polymer preferably does not contain a (meth)acrylate monomer having an aromatic group, from the viewpoint of lowering the dielectric constant of the pressure-sensitive adhesive layer. Similarly, it is possible to not only contain (meth)acrylates having an aromatic group, but also copolymerizable vinyl monomers having an aromatic group (such as styrene). In addition, from the viewpoint of avoiding influence on corrosiveness of an adherend that is easily corroded, such as the ITO surface of a transparent conductive film, it is preferable that the acid value of the acrylic polymer is 1 or less.
[0027] The polymerization method for the copolymer used as the acrylic polymer is not particularly limited, and any known polymerization method such as solution polymerization, emulsion polymerization, etc. The acrylic polymer preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylate monomer.
[0028] The properties of the pressure-sensitive adhesive composition, such as required physical properties, can be adjusted by blending a crosslinking agent and / or any appropriate additives with the acrylic polymer.
[0029] Examples of the crosslinking agent include at least one polyisocyanate compound such as biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin. The acrylic polymer preferably has a hydroxyl group as a functional group capable of crosslinking with the isocyanate compound of the crosslinking agent, and preferably contains a monomer having such a functional group in the side chain. The content of the isocyanate compound used as the crosslinking agent is preferably 0.01 to 3.0 parts by weight based on 100 parts by weight in total of the monomers belonging to the first monomer group. As the crosslinking agent, only the isocyanate compound may be used.
[0030] The pressure-sensitive adhesive composition preferably further contains a silane coupling agent. Examples of the silane coupling agent include compounds having at least one organic functional group and at least one hydrolyzable group in one molecule, the hydrolyzable group being an alkoxy group or the like bonded to a silicon atom. The silane coupling agent preferably has at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, and an amino group. Here, the (meth)acryloxy group means an acryloxy group (CH2=CHCOO-) or a methacryloxy group (CH2=C(CH3)COO-).
[0031] Examples of silane coupling agents having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 5,6-epoxyhexyltrimethoxysilane, 5,6-epoxyhexylmethyldimethoxysilane, 5,6-epoxyhexylmethyldiethoxysilane, and 5,6-epoxyhexyltriethoxysilane. Examples of silane coupling agents having a (meth)acryloxy group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, and 3-(meth)acryloxypropyldimethylmethoxysilane. Examples of the silane coupling agent having a mercapto group include 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, and 3-mercaptopropyltriethoxysilane. Examples of silane coupling agents having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-(methylamino)propyltrimethoxysilane, and 3-(methylamino)propyltriethoxysilane. Furthermore, alkoxy oligomers (silicone alkoxy oligomers) containing the above organic functional groups and oligomerized can also be used as silane coupling agents.
[0032] The content of the silane coupling agent is preferably 0.01 to 2.0 parts by weight based on 100 parts by weight in total of the monomers belonging to the first monomer group.
[0033] Other optional components include known additives such as antioxidants, surfactants, hardening accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, hardening retarders, processing aids, and antiaging agents. These may be used alone or in combination of two or more.
[0034] The pressure-sensitive adhesive layer of the present invention can be obtained by applying the pressure-sensitive adhesive composition to a substrate or a release film, and then crosslinking the pressure-sensitive adhesive composition. The gel fraction of the pressure-sensitive adhesive layer after crosslinking is preferably 40 to 75%. In addition, in order to obtain an optical pressure-sensitive adhesive layer that has good step conformability to the frame printing of the cover glass and has excellent step conformability and durability even when the cover glass and the sensor glass are bonded together, it is preferable that the pressure-sensitive adhesive layer has a storage modulus of 100000 Pa or less at 1 Hz and 100°C measured after laminating to a thickness of 1000 μm, and when a shear force of 500 Pa is continuously applied at a load of 1 N for 30 minutes, the strain is 15% or more, and the subsequent strain recovery force is 50% or more.
[0035] When used for bonding between layers of optical components, the adhesive composition preferably has an adhesive strength of 20 N / 25 mm or more, a total light transmittance of 90% or more, and a haze value of 1.0% or less when the adhesive layer after crosslinking the adhesive composition is laminated to a thickness of 175 μm on one side of a substrate. Examples of adherends used in adhesive strength tests include glass plates such as alkali-free glass, and resin films.
[0036] The pressure-sensitive adhesive layer of the present invention can be obtained by crosslinking the pressure-sensitive adhesive composition, pasting the adhesive composition onto an adherend, and curing the adhesive layer by irradiating ultraviolet light. In this case, the pressure-sensitive adhesive composition preferably contains an acrylic polymer, a crosslinking agent, a multifunctional acrylate monomer, and a photopolymerization initiator as essential components. The pressure-sensitive adhesive composition can further contain the above-mentioned silane coupling agent, etc. as an optional component.
[0037] The polyfunctional acrylate monomer is not particularly limited as long as it is a compound having 2 to 3 acryloyl groups in one molecule, and examples thereof include diacrylates of dihydric alcohols (diols), diacrylates or triacrylates of trihydric alcohols (triols), diacrylates or triacrylates of tetrahydric alcohols (tetraols), etc. Specific examples include one or more of ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, propylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, glycerol triacrylate, trimethylolethane triacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol triacrylate, etc. Similarly to the polyfunctional acrylate monomer, a polyfunctional methacrylate monomer having 2 to 3 methacryloyl groups in one molecule can also be used. One or more of these polyfunctional monomers can be used in the pressure-sensitive adhesive composition. The polyfunctional monomer used in the pressure-sensitive adhesive composition of the present invention preferably has 2 to 3 polymerizable functional groups such as (meth)acryloyl groups in one molecule. The pressure-sensitive adhesive composition does not need to contain a monomer having 4 or more polymerizable functional groups in one molecule.
[0038] The photopolymerization initiator is not particularly limited, but examples thereof include acetophenone-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzophenone-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators. Examples of the acetophenone-based photopolymerization initiator include acetophenone, p-(tert-butyl)1',1',1'-trichloroacetophenone, chloroacetophenone, 2',2'-diethoxyacetophenone, hydroxylacetophenone, 2,2-dimethoxy-2'-phenylacetophenone, 2-aminoacetophenone, dialkylaminoacetophenone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, and the like. Examples of the benzoin-based photopolymerization initiator include benzil, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-2-methylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, benzil dimethyl ketal, and 2,2-dimethoxy-1,2-diphenylethan-1-one. Examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, methyl-o-benzoylbenzoate, 4-phenylbenzophenone, hydroxylbenzophenone, hydroxylpropylbenzophenone, acrylbenzophenone, and 4,4'-bis(dimethylamino)benzophenone. Examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, diethylthioxanthone, and dimethylthioxanthone. Other photopolymerization initiators include α-acyloxime esters, benzyl-(o-ethoxycarbonyl)-α-monoxime, acylphosphine oxides, phenylglyoxylic acid esters, 3-ketocoumarin, 2-ethylanthraquinone, camphorquinone, tetramethylthiuram sulfide, azobisisobutyronitrile, benzoyl peroxide, dialkyl peroxide, and tert-butyl peroxypivalate.
[0039] By using a polyfunctional acrylate monomer, a photopolymerization initiator, and ultraviolet irradiation, the acrylic polymer crosslinked with the crosslinking agent can be further cured with ultraviolet light to improve durability. The content of the polyfunctional acrylate monomer in the pressure-sensitive adhesive composition before crosslinking is preferably 0.1 to 10 parts by weight based on 100 parts by weight of the total of the monomers belonging to the first monomer group. The content of the photopolymerization initiator is preferably 0.01 to 2.0 parts by weight based on 100 parts by weight of the total of the monomers belonging to the first monomer group. The gel fraction of the pressure-sensitive adhesive layer after ultraviolet curing is preferably 50 to 95%.
[0040] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the difference in refractive index between the pressure-sensitive adhesive layer and the optical member is as small as possible in order to reduce the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical member. For this reason, the refractive index of the pressure-sensitive adhesive layer is preferably 1.47 to 1.50.
[0041] When the pressure-sensitive adhesive layer according to the present invention is used in an electronic device such as a touch panel, from the viewpoint of reducing electromagnetic field noise, it is preferable that the pressure-sensitive adhesive layer has a relative dielectric constant of 1.50 to 5.50 and a dielectric loss of 0.01 to 0.09 at a frequency of 100 kHz, measured after being laminated to a thickness of 1000 μm.
[0042] The pressure-sensitive adhesive film of the present invention can be produced by forming the pressure-sensitive adhesive layer of the present invention on one side of a substrate or a release film. As the base film used for forming the pressure-sensitive adhesive layer and the release film (separator) for protecting the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed.
[0043] The surface of the release film that faces the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent. A "release film / adhesive layer / release film" configuration can be achieved by combining the release-treated surfaces of a release film on both sides of a single adhesive layer. In this case, the release films on both sides are peeled off sequentially or simultaneously to expose the adhesive surface, making it possible to attach it to an optical component such as an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films.
[0044] The adhesive layer of the present invention can obtain good step-following properties even when glass is laminated to glass, such as a cover glass to a sensor glass, and can be suitably used for laminating a cover glass to a sensor glass of a touch panel. In addition, when laminating a film member to a glass member, the adhesive film of the present invention obtained by laminating the adhesive layer of the present invention on one side of the film member can also be laminated to a glass member such as a cover glass or a sensor glass. The adhesive layer and adhesive film of the present invention are suitable as an adhesive layer for a touch panel and an adhesive film for a touch panel. As the step-following properties, for example, when the thickness of the adhesive layer is 175 μm, good step-following properties against a printing step of 42 μm can be mentioned.
[0045] The adhesive film of the present invention can be used for bonding various optical films for peripheral components of liquid crystal display devices, mainly polarizing plates, various optical films for touch panels, various optical films for electronic paper, various optical films for organic electroluminescence, etc. In addition, the optical film may be an optical film with a pressure-sensitive adhesive layer, in which the pressure-sensitive adhesive layer is laminated on at least one surface of the optical film.Specific examples of the optical film include structures such as "optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / release film", "optical film / pressure-sensitive adhesive layer", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film", and "release film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film". For example, in the case of "optical film / adhesive layer / release film" having an adhesive layer protected by a release film, the release film can be peeled off to expose the adhesive layer as in "optical film / adhesive layer", and then laminated with another optical film, thereby obtaining a configuration such as "optical film / adhesive layer / optical film" in which the adhesive layer is used for interlayer bonding.
[0046] The adhesive film of the present invention is preferably used for bonding a polarizing plate and a display panel. Examples of the display panel include a liquid crystal panel and an organic EL panel. The adhesive film of the present invention can be preferably used as an adhesive layer of a polarizing plate with an adhesive layer. A retardation film having a phase difference of λ / 4 or λ / 2 may be used as a constituent material of the polarizing plate. The adhesive layer of the present invention can be used for bonding a retardation film and a polarizing plate. According to the adhesive film of the present invention, since the adhesive layer has a low dielectric constant, it can be preferably used for bonding an optical member between a polarizing plate and a backlight unit in an on-cell type display device in which a touch sensor is provided between a color filter and a polarizing plate. EXAMPLES
[0047] The present invention will now be described in detail with reference to examples.
[0048] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 80 parts by weight of butyl acrylate, 20 parts by weight of methyl acrylate, 1.0 part by weight of 8-hydroxyoctyl acrylate, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution used in Example 1. A portion of the acrylic polymer was collected and used as a sample for measuring the acid value described below. [Examples 2 to 5 and Comparative Examples 1 to 3] The acrylic polymer solutions used in Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the acrylic polymer solution used in Example 1 above, except that the monomer compositions were as shown in Groups (1) and (2) in Table 1.
[0049] <Production of Pressure-Sensitive Adhesive Composition, Pressure-Sensitive Adhesive Layer, and Pressure-Sensitive Adhesive Film> [Example 1] To the acrylic polymer solution of Example 1 produced as described above, 0.5 parts by weight of Coronate L (a 75% ethyl acetate solution of a trimethylolpropane (TMP) adduct of a tolylene diisocyanate (TDI) compound) and 0.2 parts by weight of KBM-803 (3-mercaptopropyltrimethoxysilane) were added and stirred to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film (a silicone resin-coated polyethylene terephthalate (PET) film), and the solvent was removed by drying at 90°C. The adhesive composition was then aged for 7 days under an atmosphere of 23°C and 50% RH to obtain an adhesive film of Example 1 having an adhesive layer formed by crosslinking the adhesive composition on one side of the release film. [Examples 2 to 5 and Comparative Examples 1 to 3] Except for changing the composition of the additives as shown in Groups (3) to (6) of Table 1, the pressure-sensitive adhesive films of Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the pressure-sensitive adhesive film of Example 1. In the pressure-sensitive adhesive films of Examples 3 to 5 and Comparative Example 2, the pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition was irradiated with ultraviolet light for further ultraviolet curing.
[0050] [Table 1]
[0051] In Table 1, the total of the monomer group (1) consisting of alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14, alicyclic-containing monomers, and branched-structure alkyl group-containing monomers is taken as 100 parts by weight. In addition, the addition ratios of groups (2) to (6) are shown in parts by weight enclosed in parentheses. The (2) group is a monomer group consisting of a hydroxyl group-containing copolymerizable vinyl monomer and a carboxyl group-containing copolymerizable vinyl monomer. The (3) group is a crosslinking agent. The (4) group is a silane coupling agent. The (5) group is a multifunctional acrylate monomer. The (6) group is a photopolymerization initiator.
[0052] The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) L is a trade name of Nippon Polyurethane Industry Co., Ltd., D-110N and D-170N are trade names of Mitsui Chemicals, Inc., and KBM-803 (mentioned above), KBE-9007 (3-isocyanatepropyltriethoxysilane) and X-41-1805 (mercapto group-containing silicone alkoxy oligomer) are trade names of Shin-Etsu Chemical Co., Ltd. TDI means tolylene diisocyanate, TMP means trimethylolpropane, XDI means xylylene diisocyanate, and HDI means hexamethylene diisocyanate. IRGACURE® 651 (2,2-dimethoxy-1,2-diphenylethan-1-one), IRGACURE® 184 (1-hydroxy-cyclohexyl-phenyl-ketone), and DAROCUR® 1173 (2-hydroxy-2-methyl-1-phenyl-propan-1-one) are trade names of BASF.
[0053] [Table 2]
[0054] <Test methods and evaluation> The release films (silicone resin-coated PET films) were peeled off from the pressure-sensitive adhesive films of Examples 1 to 5 and Comparative Examples 1 to 3 to expose the pressure-sensitive adhesive layers, which were then evaluated by the following test and measurement methods.
[0055] <Method of measuring adhesive strength> A pressure-sensitive adhesive layer having a thickness of 175 μm was transferred onto one surface of a polyester film having a thickness of 50 μm to obtain a pressure-sensitive adhesive film (optical film with a pressure-sensitive adhesive layer) as a sample. The obtained adhesive film was laminated with a pressure roller to the non-tin surface of non-alkali glass washed with acetone, autoclaved at 50°C, 0.5 MPa for 20 minutes, and then returned to an atmosphere of 23°C and 50% RH for 1 hour. The peel strength of the adhesive film was then measured using a tensile tester in accordance with JIS Z0237 "Test method for adhesive tapes and adhesive sheets," and the peel strength when peeled in a 180° direction at a speed of 300 mm / min was taken as the adhesive strength of the adhesive layer of the adhesive film (N / 25 mm).
[0056] <Method of measuring gel fraction> The mass of the pressure-sensitive adhesive layer sample was accurately measured, immersed in toluene for 24 hours, and then filtered through a 200-mesh wire screen. The filtered material was then dried at 100°C for 1 hour, and the mass of the residue was accurately measured to calculate the gel fraction of the pressure-sensitive adhesive layer (the pressure-sensitive adhesive after crosslinking) using the following formula. Gel fraction (%) = insoluble portion mass (g) / adhesive mass (g) × 100 For the adhesive films of Examples 3 to 5 and Comparative Example 2, the gel fraction of the adhesive layer was measured after crosslinking by aging, before and after UV irradiation, with the value before UV irradiation being shown to the left of the right-facing arrow (⇒) and the value after UV irradiation being shown to the right.
[0057] <Durability test method> A 10 cm square adhesive film prepared in the same manner as in the adhesive strength measurement method was attached to the non-tin surface of alkali-free glass in the same manner to create a sample.The sample was then left in a specified atmosphere (80°C dry atmosphere, or 60°C x 90% RH atmosphere) for 250 hours, then removed from the sample and placed in a 23°C x 50% RH atmosphere.The condition of the adhesive film was visually observed after 1 hour to determine its durability. ○ The adhesive film does not peel off or foam at all. △: Peeling and bubbling have occurred in some parts of the adhesive film. × Peeling and bubbling have occurred over the entire adhesive film.
[0058] <Method for measuring storage modulus> A dynamic viscoelasticity test was carried out on a sample of the pressure-sensitive adhesive layer with a thickness of 1000 μm using a shear rheometer (Anton Paar; device name MCR301) at a frequency of 1 Hz. The measured value of the storage modulus was the value at 100° C.
[0059] <Test method for shear strain and recovery force> Using an adhesive layer with a thickness of 1000 μm as a sample, the strain A (%) was measured when a load of 1 N and a shear force of 500 Pa were maintained for 30 minutes, and the strain B (%) was measured when the shear force was then reduced to 0. The strain due to shear can be calculated by the following formula, where y is the thickness of the adhesive layer and Δx is the displacement in the shear direction (direction perpendicular to the thickness). Shear strain = (Δx / y) × 100 (%) The recovery force of strain can be calculated using the following formula: if strain B is 0% (returning to the shape before the load was applied), the recovery force is 100%, and if strain B is equal to strain A (the strain remains permanently), the recovery force is 0%. Recovery ability = (AB) / A x 100 (%)
[0060] <Test method for step-following ability> A 175 μm thick adhesive layer is laminated on the surface of a 0.7 mm glass plate, and then a 1.1 mm thick cover glass with a printing step of 42 μm is laminated from above using a vacuum lamination device under conditions of a pressure of 80 kPa and a vacuum degree of -100 kPa. Furthermore, after autoclaving at a temperature of 60° C., 6 atm, and 30 minutes, the step conformability is visually confirmed. The criteria for visual confirmation are as follows. ◯: The print step is followed and there is absolutely no foaming around the print step. △: There is a small amount of foaming around the printing step. ×: Bubbles are observed around the printing step.
[0061] <Acid value measurement method> The acid value of the acrylic polymer was measured by dissolving the sample in a solvent (a mixture of diethyl ether and ethanol in a volume ratio of 2:1) and titrating it with an automatic potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., AT-610) using a 0.1 mol / l potassium hydroxide ethanol solution. The amount of potassium hydroxide ethanol solution required to neutralize the sample was measured. The acid value was then calculated using the following formula. Acid value = (B × f × 5.611) / S B = Amount (ml) of 0.1 mol / l potassium hydroxide ethanol solution used in titration f=factor of 0.1 mol / l potassium hydroxide ethanol solution S = mass of solids in the sample (g)
[0062] <Method for measuring total light transmittance> Measurement method for light transmittance: Total light transmittance was measured according to JIS K7105, "Testing methods for optical properties of plastics."
[0063] <How to measure haze value> Measurement method of haze value: The haze value was measured according to JIS K7136, "Determination of haze of plastics-transparent materials".
[0064] Tables 3 and 4 show the evaluation results of Examples 1 to 5 and Comparative Examples 1 to 3. In the measurement results of the storage modulus in Table 3, 100,000 Pa is 1.0E+05 (1.0×10 5 ) is written as follows.
[0065] [Table 3]
[0066] [Table 4]
[0067] The pressure-sensitive adhesive layers of Examples 1 to 5 according to the present invention had a gel fraction of 40 to 75% after crosslinking, and the storage modulus at 1 Hz and 100° C. was 100,000 Pa or less when the pressure-sensitive adhesive layer was laminated to a thickness of 1,000 μm and measured. The strain was 15% or more when a shear force of 500 Pa was applied continuously for 30 minutes under a load of 1 N, and the strain recovery force was 50% or more thereafter, and the durability and step followability were excellent. In addition, when laminated to a thickness of 175 μm on one side of the substrate, the adhesive strength was 20 N / 25 mm or more, and the adhesive strength was excellent. In addition, the total light transmittance was 90% or more, and the haze value was 1.0% or less, and the optical properties were also excellent. That is, the pressure-sensitive adhesive layers of Examples 1 to 5 according to the present invention were able to overcome the requirements and problems in the prior art.
[0068] The adhesive layer of Comparative Example 1 was prepared using an adhesive composition having a low content of hydroxyl group-containing copolymerizable vinyl monomer in an acrylic polymer, and the adhesive layer had a gel fraction of 1%, low strain recovery force, and poor durability and step-following ability. The adhesive layer of Comparative Example 2 was cured with ultraviolet light using a multifunctional acrylate monomer having four acryloyl groups in one molecule, and therefore had a high storage modulus at 1 Hz and 100°C and poor durability and step-following ability. The adhesive layer of Comparative Example 3 was prepared using an adhesive composition that did not contain a crosslinking agent, and since the adhesive composition was not crosslinked, the adhesive layer had a gel fraction of 0%, low strain recovery, and poor durability and step-following ability. Thus, the pressure-sensitive adhesive layers of Comparative Examples 1 to 3 were unable to overcome the requirements and problems of the prior art.
Claims
1. a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition including an acrylic polymer, a crosslinking agent, and a silane coupling agent; The acrylic polymer is (A) an alkyl acrylate monomer having an alkyl group with a carbon number of 1 to 14, (B) an alicyclic-containing monomer, (C) a branched-structure alkyl group-containing monomer, and (D) a nitrogen-containing vinyl monomer; (E) 0.1 to 10.0 parts by weight of at least one hydroxyl group-containing copolymerizable vinyl monomer in total; The alkyl group of the alkyl acrylate monomer (A) having a carbon number of C1 to C14 is linear, the (B) alicyclic-containing monomer is an alicyclic alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C18; the branched alkyl group-containing monomer (C) is a branched alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C18; The nitrogen-containing vinyl monomer (D) does not contain a hydroxyl group, the (E) hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; The acid value of the acrylic polymer is 1 or less, the crosslinking agent is an isocyanate compound, the pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a gel fraction of 40 to 75%; The pressure-sensitive adhesive layer is characterized in that, when the pressure-sensitive adhesive layer is laminated to a thickness of 1,000 μm and measured at 1 Hz and 100° C., the layer has a storage modulus of 100,000 Pa or less, and when a shear force of 500 Pa is applied to the layer at a load of 1 N for 30 minutes, the layer has a distortion of 15% or more, and has a subsequent distortion recovery force of 50% or more.
2. An adhesive film for a touch panel, comprising the adhesive layer according to claim 1 laminated on one surface of a substrate.
3. An optical film with a pressure-sensitive adhesive layer, comprising an optical film and the pressure-sensitive adhesive layer according to claim 1 laminated on at least one surface of the optical film.
Citation Information
Patent Citations
Display device, method for manufacturing display device, and electronic equipment
JP2009098324A
Transparent adhesive sheet, image display apparatus comprising the same, and method for producing the image display apparatus
JP2010072471A
Transparent pressure-sensitive adhesive sheet for flat panel display, and flat panel display
JP2010097070A
Adhesive composition and optical member using the same
JP2010150396A
Adhesive, adhesive layer, and adhesive sheet
JP2012246477A